PELAKSANAAN PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI KECAMATAN RUMBAI PESISIR TAHUN 2018-2019 - Ulfa "; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The implementation of the Systematic Complete Land Registration Program (PTSL) has begun in 2017. The implementation of the PTSL Program is carried out in accordance with Ministerial Regulation ATR / BPN Number 12 of 2017 concerning the Acceleration of Systematic Complete Land Registration.  The PTSL program aims to accelerate the provision of legal certainty and legal protection of community land rights with certainty so that it can improve the welfare and prosperity of the people in Pekanbaru City.  Rumbai Pesisir District is the district with the least number of PTSL arrangements so the target provided is not achieved.               The purpose of this study is to describe the implementation of the Systematic Complete Land Registration Program (PTSL) in the Rumbai Coastal District, then also to determine the inhibiting factors for the implementation of the Systematic Complete Land Registration Program (PTSL) in the Rumbai Coastal District in 2018-2019.               The theoretical concept used is the theory of policy implementation by Merilee S. Grindle.  This type of research is a qualitative descriptive.  Data collection techniques are done by interview and documentation.               The results of this study are that the implementation of the Systematic Complete Land Registration Program (PTSL) in the Rumbai Coastal District is not optimal.  The inhibiting factors in the implementation of the PTSL Program are the lack of resources used, the intended resource is the lack of measurement officers.  The mindset of the community, where people think that by joining the PTSL Program, the tax affected will be high.  Lack of counseling conducted by officers of the Land Office, counseling is only done once at the village level.  Late implementation time and boundary markers are not installed. Keywords: Implementation, Systematic Complete Land Registration Program (PTSL)